Analisis nilai perusahaan pada perusahaan textile dan garmen yang terdaftar di BEI - Muhammad Febri Wijaya; Dhani Ichsanuddin Nur (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
The purpose of this study is to determine and analyze the effect of capital structure, sales growth, profitability, company size as factors considered by the company on the firm value of textile and garment companies listed on the Indonesia Stock Exchange for the period 2016 – 2019. This study uses quantitative and qualitative methods. using linear regression analysis using the SPSS program as a testing tool. The results of this study indicate that the independent variable, namely capital structure, can contribute to determining firm value. Sales growth cannot contribute in determining the value of the company. Profitability can contribute in determining the value of the company. While the size of the company can contribute to determining the value of the company